ANTHROPOCENTRIC INTERPRETATION OF UNIVERSAL CONCEPTS IN ENGLISH AND UZBEK LITERARY DISCOURSE - Gunel Hummetova (Paniyeva) Saleh,Mamatqulova Xolida Axtamovna (International Journal of Literature and Language Studies, 2026)
This article studies the anthropocentric interpretation of universal concepts in English and Uzbek literary discourse. It examines how literary texts place the human being at the center of conceptualization and how personhood, memory, time, family, love, and moral choice structure artistic meaning. The research uses Khalida Mamatkulova’s ideas about universal concepts, typological similarity, worldview, and national identity. The article argues that both traditions represent the world through human experience, emotion, and value while constructing the human being through culturally specific models of selfhood and responsibility.